Digital skills: Academics at a South African University in post-COVID-19 era - Mpungose, C. B. (South African Journal of Higher Education, 2024)
Academics from South African Universities have recently been bound to possess digital skills for curriculum delivery due to the lessons learned from the COVID-19 era. Universities have implemented various interventions to enhance digital skills in academics, which include but are not limited to training workshops, organised webinars, and seminars. Irrespective of these interventions, some academics still lack the digital skills to deliver effective digital curricula. The primary aim of the research is to develop other methods to address the shortage of digital skills among scholars. This research is based on a three-year qualitative interpretive study carried out at a university in South Africa, exploring a scenario where academics share their experiences on utilising digital platforms for teaching and learning following the COVID-19 pandemic. Data was generated purposefully and conveniently by sampling thirty-two academics from the school of education. The methods used for data generation included e-reflective activities, Zoom group discussions, and semi-structured interviews conducted one-on-one via WhatsApp. After thematic analysis, findings show that academics’ digital background becomes the barrier to having the necessary digital skills for digital curriculum delivery. Hence, most of them were driven by informal skills for social needs and personal digital skills for individual needs at the expense of formal digital skills for discipline needs. With universities in developing countries still becoming victims of student protests, natural disasters, and other challenges, alternatives are being sought to accommodate the transition from face-to-face to online or hybrid curriculum delivery modes.